MUZIKA OQÍTÍWSHÍSÍNÍŃ SÓYLEW MÁDENIYATÍ SABAQTÍŃ TÚSINIKLI BOLÍWÍNÍŃ DEREGI (ART AND CULTURE BULLETIN, 2024)
In the process of teaching and educating a teacher, a teacher's correct, civilized andclear communication ability is highly valued. A music teacher, in the sense of his professional competence,should convey the laws of ethics to children and ensure the optimal development of each child. Therefore,this article is about the culture of the music teacher.
Keywords: music; education; speech information; educationetiquette; manners; competence; optimal; speech literature; intellectual.